Efficiency and performance ratio of photovoltaics on a 50 kWp Universitas Pamulang Viktor rooftop solar power plant - Rozak, Ojak Abdul; Triyanto, Aripin; Kusnadi, Heri (Bulletin of Electrical Engineering and Informatics, 2024)
To overcome the fossil energy crisis due to the increasing need for electrical energy, new renewable energy sources are needed. Due to technological developments in the fields of transportation, industry, household, and commercial use. Indonesia’s geography has the potential to apply new renewable energy, more specifically photovoltaic (PV). However, it is greatly influenced by environmental factors such as solar radiation, voltage, which have an impact on the output power efficiency and performance. So, it is necessary to test both measurements and calculations to see the optimization of output power and PV efficiency. From previous research, it has not been carried out, especially in the experimental method Universitas Pamulang: measurement and empirical and for a sufficiently high capacity with the aim of optimal output power. Methods of measuring sunlight intensity, voltage and current, the calculation of converting sunlight intensity to solar constellation, power, efficiency, and performance ratio (PR). The average value being 721 W/m2 an efficiency value of 19.9% and a value PR is obtained of 0.967 or 96.7% is still realistic. So that the system is declared optimal.